2022
DOI: 10.1155/2022/5895560
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Corporate Capital Structure on Financial Performance Based on Convolutional Neural Network

Abstract: Capital structure is an important indicator to measure the source, composition, and proportion of a company’s equity and debit capital. It is not only related to the internal operating environment of listed companies but also related to the rights and obligations of shareholders and is closely related to the company’s future development direction, decision-making bodies, and changes in governance structure. This study aims to study the impact of corporate capital structure on financial performance based on con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…One article notes that financial capital is often guided by its real counterpart, meaning that it can influence the direction of the business (Dinets et al, 2020). Another study found that the impact of corporate capital structure on financial performance can be studied using convolutional neural networks (Luo & Jiang, 2022). Managing financial capital is important for the long-term success of a business.…”
Section: Financial Capital and Entrepreneurshipmentioning
confidence: 99%
See 2 more Smart Citations
“…One article notes that financial capital is often guided by its real counterpart, meaning that it can influence the direction of the business (Dinets et al, 2020). Another study found that the impact of corporate capital structure on financial performance can be studied using convolutional neural networks (Luo & Jiang, 2022). Managing financial capital is important for the long-term success of a business.…”
Section: Financial Capital and Entrepreneurshipmentioning
confidence: 99%
“…A quantitative design is suitable for this research because it involves collecting numerical data that can be analyzed statistically. This type of design is useful for testing hypotheses and determining the relationships between variables (Luo & Jiang, 2022). The four constructs that are being measured in this research are social capital, financial capital, entrepreneurial orientation, and performance.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 1 more Smart Citation